Using Customer Journey Mapping and Design Thinking to Understand the Library’s Role in Supporting the Research Data Lifecycle - Kay Bjornen (University of Massachusetts Medical School, Lamar Soutter Library, 2021)
Objective: Customer journey mapping and design thinking were identified as useful tools for identifying deeper insights into the research data service needs of researchers on our campus with their direct input. In this article we discuss ways to improve the process in order to identify data needs earlier in the project life and at a more granular level.